Methods and Applications of CRISPR-Mediated Base Editing in Eukaryotic Genomes - Hess, G.T.; Tycko, J.; Yao, D.; Bassik, M.C.
The past several years have seen an explosion in development of applications for the CRISPR-Cas9 system, from efficient genome editing, to high-throughput screening, to recruitment of a range of DNA and chromatin-modifying enzymes. While homology-directed repair (HDR)coupled with Cas9 nuclease cleavage has been used with great success to repair and re-write genomes, recently developed base-editing systems present a useful orthogonal strategy to engineer nucleotide substitutions. Base editing relies on recruitment of cytidine deaminases to introduce changes (rather than double-stranded breaks and donor templates)and offers potential improvements in efficiency while limiting damage and simplifying the delivery of editing machinery. At the same time, these systems enable novel mutagenesis strategies to introduce sequence diversity for engineering and discovery. Here, we review the different base-editing platforms, including their deaminase recruitment strategies and editing outcomes, and compare them to other CRISPR genome-editing technologies. Additionally, we discuss how these systems have been applied in therapeutic, engineering, and research settings. Lastly, we explore future directions of this emerging technology. CRISPR-mediated base editing relies on recruitment of cytidine deaminases to introduce either precise C>T or diverse C>N changes, while avoiding nuclease-mediated double-strand breaks. Here, we review the different base editing platforms, including their deaminase recruitment strategies and editing outcomes, and discuss their application in therapeutic, engineering, and research settings.
Keywords: DEAMINASE; ENDONUCLEASE; GUIDE RNA; NUCLEOTIDE